Trauma Profile of Homicide Victims at Dr. Soetomo General Academic Hospital, Surabaya, during the COVID-19 Pandemic - Syarif, Ichsan; Yudianto, Ahmad; Saleh, Tania Ardiani; Sulistyorini, Nily (Universitas Airlangga, 2024)
Highlights: Most homicide victims were predominantly in the productive age range of 21-40 years old. Males were more likely to be homicide victims than females. Abstract Introduction: The injuries of homicide victims are clues in forensic medicine to uncover a possible crime. In Indonesia, there are not many studies on trauma profiles, specifically in homicide cases. This study aimed to provide an overview of the trauma profile of homicide victims at Dr. Soetomo General Academic Hospital, Surabaya, from January 2020 until December 2021. Methods: This was a descriptive study. Secondary data was collected from 34 forensic examination reports at Dr. Soetomo General Academic Hospital, Surabaya. Data such as age, sex, type of injury, sites of injury, number of injuries, cause of death, and mechanism of death were analyzed statistically. Results: Most victims were between 21 and 30 years old and 31 and 40 years old (26.47%). Sex was dominated by men (76.47%). The most common type of injury was abrasion (25.71%). The most common injury sites were head-neck (34.34%) and chest-upper back (34.34%). The most common number of injuries was â‰¥10 (44.12%). The most common cause of death was sharp-force trauma (54.54%), and the most common mechanism of death was exsanguination (54.54%). Conclusion: Males predominated in the age ranges of 21 to 30 years old and 31 to 40 years old. The most common type of injury was abrasion. The most common sites of injury were the head, neck, and chest upper back. The most common number of injuries was â‰¥10. Most victims died of sharp-force trauma. Exsanguination was the most common mechanism of death.